Phylogenetically diverse diets favor more complex venoms in North American pitvipers - Holding, Matthew; Parkinson, Christopher (Dryad, 2020)
The role of natural selection in the evolution of trait complexity can be
characterized by testing hypothesized links between complex forms and
their functions across species. Predatory venoms are traits composed of
multiple proteins that collectively function to incapacitate prey. Venom
complexity fluctuates considerably over evolutionary timescales, with
apparent increases and decreases in complexity, yet the evolutionary
causes of this variation is unclear. Here, we tested alternative
hypotheses for the link between venom complexity and ecological sources of
selection related to diet in the largest clade of front-fanged
venomous snakes in North America: the rattlesnakes, copperheads, cantils,
and cottonmouths Crotalus, Sistrurus and Agkistrodon. We generated
independent transcriptomic and proteomic measures of venom complexity and
then estimated prey diversity using the past century's extensive
natural history studies on these snakes. We then conducted comparative
tests relating  different measures of predator venom complexity
and prey community diversity using the first, genome-scale, dated
phylogenies for this clade of snakes. Strikingly, phylogenetic diversity
of prey was more strongly correlated to venom diversity than was species
diversity, implicating prey species divergence, rather than the number of
lineages alone, in the evolution of venom complexity. This positive
relationship was observed within three of the four largest toxin gene
families in viper venom. Given documented examples of taxonomic
specificity of venoms spanning several levels of divergence,
we suggest that the phylogenetic diversity of prey measures
functionally-relevant divergence in the molecular targets of
venom, a claim supported by diversity in the coagulation cascade targets
of snake venom serine proteases. Our results support the general
concept that the evolved diversity of species in an ecological community
is more important than their overall number in determining evolutionary
patterns in predator trait complexity.
Venom-gland transcriptomes were subject to Trinity assembly and BUSCO v.3
search for orthologous genes. Alignments were produced using MAFFT and
trimmed with trim-al. See manuscript for additional details.
Keywords: Evolutionary biology; venom; Diet Breadth; Crotalus